Scaling effect of interfacial reaction on intermetallic compound formation in Sn/Cu pillar down to 1 μm diameter. (15th September 2016) - Liu, Yingxia; Chu, Ying-Ching; Tu, K.N.
Abstract: Different diameter Sn/Cu pillars varying from 30 to 1 μm have been made by focus ion beam, and the solid state reaction to form Cu6 Sn5 in these pillars has been studied. An increased Cu-Sn reaction rate to form Cu6 Sn5 was observed as the pillar diameter decrease from 20 to 1 μm when annealed at 185 and 195 °C. With the shrinking of pillar size, surface diffusion becomes important as compared to grain boundary and lattice diffusion in the Cu-Sn interfacial reaction. Also, surface diffusion induced Kirkendall voids was observed to locate at the peripheral area just above Cu of the Cu-Sn pillars. A simple kinetic model of surface diffusion controlled intermetallic compound growth of Cu6 Sn5 is proposed for pillars with diameter below 5 μm. What is essential in the model is that we assume a rapid interstitial diffusion of Cu in Sn, and we are able to calculated surface diffusivity of Cu on Cu6 Sn5 . At 185 °C, the surface diffusivity is about 3.1 × 10 −7  cm 2 /s and the activation energy is about 0.2 ± 0.1 eV/atom. Graphical abstract: